Pediatric Endoscopy Quality Improvement Network Quality Standards and Indicators for Pediatric Endoscopists and Endoscopists in Training: A Joint NASPGHAN/ESPGHAN Guideline. (16th March 2022) - Walsh, Catharine M.; Lightdale, Jenifer R.; Leibowitz, Ian H.; Lerner, Diana G.; Liu, Quin Y.; Mack, David R.; Mamula, Petar; Narula, Priya; Oliva, Salvatore; Riley, Matthew R.; Rosh, Joel R.; Tavares, Marta; et al.
ABSTRACT: Introduction: High-quality pediatric endoscopy requires reliable performance of procedures by competent individual providers who consistently uphold all standards determined to assure optimal patient outcomes. Establishing consensus expectations for ongoing monitoring and assessment of individual pediatric endoscopists is a method for confirming the highest possible quality of care for such procedures worldwide. We aim to provide guidance to define and measure quality of endoscopic care for children. Methods: With support from the North American and European Societies of Pediatric Gastroenterology Hepatology and Nutrition (NASPGHAN and ESPGHAN), an international working group of the Pediatric Endoscopy Quality Improvement Network (PEnQuIN) used the methodological strategy of the Appraisal of Guidelines for REsearch and Evaluation (AGREE) II instrument to develop standards and indicators relevant for assessing the quality of endoscopists. Consensus was sought via an iterative online Delphi process and finalized at an in-person conference. The quality of evidence and strength of recommendations were rated according to the GRADE (Grading of Recommendation Assessment, Development, and Evaluation) approach. Results: The PEnQuIN working group achieved consensus on 6 standards that all providers who perform pediatric endoscopy should uphold and 2 standards for pediatric endoscopists in training, with 7 corresponding indicators that can be used to identify high-quality endoscopists. Additionally, these can inform continuous quality improvement at the provider level. Minimum targets for defining high-quality pediatric ileocolonoscopy were set for 2 key indicators: cecal intubation rate (≥90%) and terminal ileal intubation rate (≥85%). Discussion: It is recommended that all individual providers performing or training to perform pediatric endoscopy initiate and engage with these international endoscopist-related standards and indicators developed by PEnQuIN.